ANALISIS HARGA SAHAM SEBELUM, SAAT, DAN SETELAH AKSI DEMO 411 DAN AKSI DEMO 212 TAHUN 2016 - Wirawan Suhaedi; Nurabiah Nurabiah; Ika Putri Fitri Anjani (Jurnal Riset Akuntansi, 2017)
The 411 and 212 rally related to the issue of religious blasphemy has drawn the attention of Indonesian people and also became the news of the world. Both events cause some positive and negative perceptions of society and government as well as the investors since it will likely impact the stock price in Indonesia capital market as represented by value of abnormal return. Therefore, this study aimed to prove the presence or absence of the impact of both events to the stock price. This study was conducted on 100 samples of companies listed on the Kompas 100 index during August 2016 - January 2017. This research is a comparative descriptive study by using event study approach. The test was performed by using Wilcoxon one sample test and Wilcoxon paired samples test. The results of this study indicate that the stock prices tend to fall before the 411 rallies took place. Although the event did not have an impact on stock price changes at the time of the 411 rallies happened, the stock prices tend to rise after the action of 411 rallies took place. The results of this study also indicate that the stock prices tend to fall before until the 212 rallies took place then tend to rise after the action of 212.